A dois passos do paraíso?: análise sobre a construção da favela Paraisópolis (São Paulo-SP) como destino turístico - Borges, Andréa Maria Abreu (2012)
This thesis deals with the construction of the Paraisópolis slum (São Paulo-SP) as a tourist destination. Estevão, Ber bela and Antenor, slum dwellers, perform 'artworks' which represent the main elem ent of the tourist attractiveness of Paraisópolis. From the field work, as a participatory observation, I describe the divergent attitudes of ar tists, tourist guides and th e Residents' Union of Paraisópolis. I point that these attit udes generate symbolic di sputes and power relations among the actors involved in the process of transformation of Paraisópolis into a tourist destination. The main guideline is to understand how this process can be affected by conflicts , whether due to polit ical, economic or ideological issues. The perspective of analysis focuses on the central disputed views on tourism and the practices in whic h are based on. Thus, I am trying to understand how the local values and practices are articulated with exogenous speeches and actions geared to the development of tourism.